An analysis of factors which affect faculty-librarian relationship in book selection at the De La Salle University Library - Leonardo, Rapunzel V. (2003)
The study was conducted in order to analyze the factors which affect faculty-librarian relationship in book selection at the De La Salle University Library. It was hypothesized that: (1) there is no significant difference in the faculty and librarian relationship in book selection with reference to the following factors: years of recommending books; average number of books ordered yearly; audience of book selection; purpose of book selection; criteria of book selection; sources utilized in book selection; ways of participation in book selection; allocation of book budget per department.